Evaluation of Microdesmis puberula Leaf Meal as Feed Ingredient in Laying Hen Diets - Esonu, B.O.; Azubuike, J.C.; Ukwu, H.O. (International Journal of Poultry Science, 2004)
A fifty-day feeding trial was conducted to evaluate the leaf meal of Microdesmis puberula as feed ingredient in laying hen diets. Microdesmis puberula is a preferred tropical browse plant. Seven experimental layers diets were formulated incorporating the leaf meal of Microdesmis puberula at 0.0, 2.5, 5.0, 7.5, 10.0, 12.5 and 15.0% dietary levels. One hundred and five (105), Shikka brown layers already 10 months in lay were divided into 7 groups of 15 birds each and randomly assigned to the 7 treatment diets in a completely randomized design (CRD). There were no significant differences (p<0.05) in body weight, Haugh unit, Shell thickness, Yolk index and Albumin index among the groups. However, there were significant (p<0.05) differences among the groups in hen-day egg production, egg weight, feed intake, egg size and dressed carcass weight. The intensity of the egg yolk colouration increased with increasing levels of the leaf meal in the diets. The results of this study suggest that 15% dietary inclusion of Microdesmis puberula leaf meal could be used in layers diets without any deleterious effects on performance.